The Correlation Between Students’ Self-Confidence and Students’ Speaking Ability in English - Jannah, Miftahul; Jabu, Baso; Sakkir, Geminastiti (Journal of Excellence in English Language Education, 2024)
This study examines the correlation between students' self-confidence and English-speaking ability. It will be accomplished using two distinct instruments: a questionnaire assessing students' dread of writing and a speaking examination centered on memorable moments. This study aims to determine the relationship between students' self-confidence and their speaking skills. This investigation utilized a correlational quantitative research approach—this study's sample comprised one hundred Class XI students from SMA Negeri 1 Pinrang. Cluster random sampling was also used during the sampling procedure. This method permits selecting a sample representative of the population, ensuring that the representation is accurate. The research demonstrates a significant correlation between self-confidence and speaking abilities, indicating a positive relationship between these variables. However, as students' self-confidence increases, their speaking proficiency improves proportionally.